The impact of geriatric nutritional risk index on esophageal squamous cell carcinoma patients with neoadjuvant therapy followed by esophagectomy - Fang, Pinhao; Yang, Qian; Zhou, Jianfeng; Yang, Yushang; Luan, Siyuan; Xiao, Xin; Li, Xiaokun; Gu, Yimin; Shang, Qixin; Zhang, Hanlu; Chen, Longqi; Zeng, Xiaoxi; et al. (Frontiers in Nutrition, 2022)
Background: The Geriatric Nutritional Index (GNRI) has been indicated as a nutritional index which is highly associated with complications and mortality in older hospitalized patients. Moreover, early studies had suggested that GNRI is a potential prognostic indicator for some malignances. However, the prognostic value of GNRI in EC patients underwent neoadjuvant therapy followed by esophagectomy remains elusive. Methods: This retrospective study incorporated 406 patients with esophageal cancer (EC) who had underwent neoadjuvant therapy followed by radical esophagectomy at West China Hospital of Sichuan University between April 2011 and September 2021. The GNRI formula was: 1.489×albumin (g/dl)+41.7×current weight/ideal weight. Patients were classified as GNRI-low (GNRI<98) or GNRI high (GNRI> 98). The association between GNRI and clinical survival status were assessed utilizing Kaplan-Meier methods and Cox regression analysis. Results: 406 patients were retrospectively included in this study. 80 (19.7 %) and 326 (80.3 %) patients had been divided into the GNRI-low and GNRI-high groups respectively. Pathological T stage and the rate of nodal metastasis were significantly higher in the GNRI low group than in the GNRI high group (P<0.001 and P<0.001, respectively) among the examined demographic parameters. Furthermore, GNRI was significantly correlated with postoperative complications, patients with lower GNRI had a higher postoperative complication rate as compared with GNRI high group [Odds ratio: 2.306; 95 % confidence interval (CI): 1.246–4.266; P=0.008]. Univariate analysis of 5-year overall survival (OS) and disease-free survival (DFS) found that the rate of survival was considerably lower in the GNRI-low group than in the GNRI-high group (P<0.001). However, multivariate analysis demonstrated that GNRI was not an independent risk factor. Conclusion: In patients with EC, low GNRI exhibited a poor nutritional indicator and related to postoperative complications after neoadjuvant therapy. Intensive follow-up after surgery should be performed for EC patients with low GNRI.